2008
DOI: 10.1139/x07-185
|View full text |Cite
|
Sign up to set email alerts
|

Growth response following green crown pruning in plantation-grown Eucalyptus pilularis and Eucalyptus cloeziana

Abstract: Pruning of live branches is performed to enhance wood quality in plantation trees. Stem, branch and wood properties may be altered following pruning from below, but the extent and duration of such effects are unknown for many plantation Eucalyptus species. The effect of 0%, 20%, 50%, and 70% green crown length removal on growth and wood quality was examined in 3.5-year-old plantation-grown Eucalyptus pilularis Sm. (blackbutt) and Eucalyptus cloeziana F. Muell. (Gympie messmate) trees on two subtropical sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 15 publications
(23 reference statements)
3
29
0
Order By: Relevance
“…However, given the rapid recovery of transpiration rates, determining the best time to prune these fast-growing eucalypts in order to achieve the maximum drought-buffering effect requires further study. The minor and insignificant reduction in diameter growth is consistent with other pruning studies on E. pilularis and E. cloeziana that removed the lower 50% of the live-crown length [30]. Pruning also had no significant effect on the above-ground biomass growth of the largest 200 trees ha −1 of E. nitens trees, 2-3 years after pruning [31].…”
Section: Discussionsupporting
confidence: 87%
“…However, given the rapid recovery of transpiration rates, determining the best time to prune these fast-growing eucalypts in order to achieve the maximum drought-buffering effect requires further study. The minor and insignificant reduction in diameter growth is consistent with other pruning studies on E. pilularis and E. cloeziana that removed the lower 50% of the live-crown length [30]. Pruning also had no significant effect on the above-ground biomass growth of the largest 200 trees ha −1 of E. nitens trees, 2-3 years after pruning [31].…”
Section: Discussionsupporting
confidence: 87%
“…If pruning is required, then the cost of this action increases with increasing branch size and frequency, with wounds taking longer to overgrow on larger branches (Smith et al 2006). In addition to this, larger branch knots result in greater levels of degrade in the final product (Alcorn et al 2008). The frequency of ramicorns was also reduced when susceptibility to Q. pitereka was low.…”
Section: Discussionmentioning
confidence: 98%
“…Brendenkamp et al, 1983;Pinkard and Beadle, 2000;Monte et al, 2009). A general consensus is that 40 to 50% of the lower green crown can be removed without affecting tree growth (Pinkard and Beadle, 1998;Alcorn et al, 2008;Forrester et al, 2010). The results found in this study indicated a stronger response of growth loss following pruning than usual, with mean stand attributes suffering reduction with the removal of 40% of lower green crown onwards.…”
Section: Discussionmentioning
confidence: 53%